Degradação do antibiótico metronidazol por processos oxidativos avançados. - Silva, Schirlei Diana Kleinubing (2016)
The photodegradation of antibiotic metronidazole (MNZ) in aqueous solution using ultraviolet light, was investigated in the presence of hydrogen peroxide (H2O2) and catalysts: titanium dioxide (TiO2) and zinc oxide (ZnO). The photocatalytic tests in the presence of (H2O2) were carried out at different pH values 4, 7 and 10. In the photocatalysis heterogeneous experiments, an experimental design 23 was performed to evaluate the influence of variables: pH, hydrogen peroxide concentration and concentration of catalyst in the fotodegradation of drug wich was monitored by spectrophotometry in the UV-VIS region. The kinetic model of first order described well the behavior of degradation of drug. In photocatalysis results in the presence of hydrogen peroxide, the maximum degradation rate was 8.66% at pH 4. Statistical analysis showed that the photocatalysis experiments with heterogeneous titanium dioxide only the variable interaction of pH/H2O2 had no a significant effect. The maximum degradation rate was 72.1% to MNZ when employed in the TiO2 catalyst concentration of 100 mg L-1 and H2O2 at 1000 mg L-1 at pH 10. In heterogeneous photocatalysis with zinc oxide, the variables interactions pH/ H2O2 and H2O2 / ZnO have no significant effects. Higher rate of degradation of MNZ using ZnO as catalyzer was 59.58%, the same conditions used with TiO2 catalyst.